IMPACT OF COVID-19 UPON THE MENTAL HEALTH OF HEALTHCARE WORKERS AND STUDENTS IN PAKISTAN: REVIEW ARTICLE - Mustafa, Ali Burhan; Mustafa, Saima; Saleem, Mussarat (Journal of Pakistan Psychiatric Society, 2022)
Background: The pandemic COVID-19 affected all sections of society globally including Healthcare workers (HCWs). The numerous studies showed the negative impact of COVID upon the mental health of healthcare workers and healthcare students in Pakistan. Methods: Cross sectional studies of 12 articles selected out of which, 09 articles from Pakistan included. These articles were published in various journals of good impact factor. The two psychometric tools and questionnaires used to assess the prevalence. The participants included Healthcare workers, students, and graduates. Results: Of the studies included, 64.3% HCW graduates followed by 44.9% nurses, 44.5% doctors and 35.7% students. Female HCWS, frontline HCWS, nurses, young staff were more likely to suffer from mental health issues, i.e., anxiety and depression. Conclusion: During the recent pandemic COVID-19, a considerable number of HCWS struggled through various mental health issues. The findings call for a workable psychological intervention model especially designed for HCWS. Keywords: COVID-19, healthcare workers, mental health